Simple Pulmonary Eosinophilia Caused by Ascaris Lumbricoides (Loeffler's Syndrome): Case Report - Okutan, Oğuzhan; Ugan, Harun; Kartaloğlu, Zafer; Kunter, Erdoğan; Sezer, Oğün (Fırat University, 2007)
Loeffler's syndrome (simple pulmonary eosinophilia) is a syndrome which is characterized by peripheric eosinophilia and transient pulmonary opacities on chest radiograph. Our patient who was twenty-one years old, and had symptoms like dsypnea, coughing, chest pain and hemoptysis in a episodic way for five months, was hospitalized. We oscultated polyphonic rhonchuses at the both hemithoraxes. Heterogen opacities on the different locations on chest radiography were seen and peripheric leucocytosis was detected at the whole blood count. There was combined type disorder of pulmonary function test (PFT). We gave nonspecific antibiotics and bronchodilators to the patient at the beginning. The patient who was fine with the treatment, came to the our clinic with the same symptoms after two month of discharge. We got the same physical examination findings as before, patchy focal ground-glass opacities were seen at the apexes of the both lungs, at the anterior segment of upper lobe of right lung, at the middle lobe of right lobe, at the lingular segment of left lung and at the superior segments of both lower lobes by Thorax high resolution computerized tomography (HRCT). Bronchoscopy was done. Microbiological examinations of samples which were gotten by bronchoscopy were negative, total Eo 800 /mm3 and total IgE 116 were measured, eosinophilia on sputum and nasal smear was not detected. Nasal poliposis and sinusitis were diagnosed by ENT specialist and conjunctivitis was diagnosed by eye specialist. Ascarid eggs were detected from the stool. We gave albendazol 500 mg one-dose, regarding the patient as Loeffler's syndrome. The anormalities on chest radiograph disappeared after the treatment. ©2007, Fırat Üniversity, Medical Faculty

Loeffler's sendromu (basit pulmoner eozinofili) akciğer grafisinde gezici pulmoner infiltratlar ve periferik eozinofili ile karekterize bir klinik tablodur. Olgumuz, yirmi yaşında erkek olup, yaklaşık beş aydır aralıklarla ortaya çıkan nefes darlığı, öksürük, göğüs ağrısı, kanlı balgam çıkarma şikayetleri ile kliniğimize yatırıldı. Solunum sistemi muayenesinde her iki hemitoraksda polifonik ronküsler duyuldu. Hemogramında lökositoz saptanan hastanın PA akciğer grafisinde farklı lokalizasyonlarda heterojen dansite artımları izlendi. Solunum fonksiyon testinde kombine tip fonksiyon bozukluğu saptandı. Hastaya nonspesifik antibiyoterapi ve bronkodilatör tedavisi başlandı. Bulgu ve şikayetleri düzelen hasta taburcu olduktan yaklaşık iki ay sonra tekrar aynı şikayetler ile kliniğimize başvurdu. Fizik muayene bulguları ilk yatırılışındaki ile aynı olup çekilen yüksek çözünürlüklü bilgisayarlı tomografisinde (YÇBT) de, her iki akciğer apeksde, sağ akciğer üst lob anterior segmentte, sağ akciğer orta lob, sol akciğer lingular segment ve her iki akciğer alt lobda superior segmentlerde yamalı buzlu cam dansitesinde fokal parankim sahaları izlendi. Hastaya bronkoskopi yapıldı. Alınan örneklerin mikrobiyolojik ve patolojik incelemelerinde bir özellik saptanmadı. Hastanın total eozinofil sayımı 800/mm3 ve total IgE 116 olup, balgamda ve nazal smearde eozinofil saptanmadı. Üst solunum yollarının muayenesinde nazal polipozis ile sinüzitis ve göz muayenesinde konjunktivit saptandı. Hastanın gaita analizinde ascaris lumbricoides yumurtaları görüldü. Loeffler's sendromu olarak değerlendirilen hastaya tedavi olarak albendazol 400 mg. tek doz verildi. Tedavi sonrasında lezyonlar tamamen kayboldu. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Ascaris Lumbricoides'e Bağlı Basit Pulmoner Eozinofili (Loeffler's Sendromu): Olgu Sunumu